The Satisfaction of Students about How Instructional Design Quality Criteria for e-Course in Distance Learning - Ibrahim, Hatim (International Journal of Educational Technology and Learning, 2020)
The purpose of this study is to know the level of satisfaction of Students about how instructional design quality criteria for e-course in distance learning University Imam Abdul Rahman bin Faisal, as the current study aimed to build standards for quality instructional design for e-learning courses via the Internet, this is achieved through the following objectives: identifying key areas in which they can regulate the quality of instructional design for e-learning courses via the Internet, and identify instructional design quality evaluation criteria for such courses and organize them in categories And touchstones to verify meet standards, and building a list of quality criteria for instructional design and indicators for design courses, and propose a method for assessing and measuring electronic Provided by meeting quality criteria for instructional design. And might form a community of Students study e-learning programs for associate University Imam Abdul Rahman bin Faisal, the study found a total of results. Results of the test (t) between the middle grades of respondents (Students have experience in computer skills/experience Students medium to Low in computer skills) to measure satisfaction, value (v) is a statistical function, test results (v) between the middle grades of respondents (average high school/academic rate low) on the scale of satisfaction, value (v) is a statistical function, the test results also showed (v) between the middle grades of respondents (male/female) on a scale of satisfaction, value (v) statistical function at a level (0.01), and calculate the value (=) found it not exceeding (0.02), and this shows that small effect size, and then It cannot be said that there are substantial differences between the sexes (males/females) in the level of satisfaction, satisfaction level the satisfaction of Students in e-learning programs associated with the University of Imam Abdul Rahman bin Faisal one low Provided by environment, as showing a high satisfaction level in the all the vocabulary of first, second and third dimension refers in its entirety to the level of satisfaction is high as the average satisfaction level found in all the vocabulary of fourth, fifth and sixth dimension refers in its entirety to the average satisfaction level, as Low satisfaction level found in all dimension vocabulary VII and VIII IX refers in its entirety to the low satisfaction level, in the light of the Findings of the study, the researcher made many recommendations and proposals.